Anakinra treatment in multisystemic inflammatory syndrome in children (MIS-C) associated with COVID-19 - Çaǧlayan, Şengül; Sönmez, Hafize Emine; Otar Yener, Gülçin; Baǧlan, Esra; Öztürk, Kübra; Ulu, Kadir; Guliyeva, Vafa; Demirkol, Demet; Çakan, Mustafa; Özdel, Semanur; Bukulmez, Hulya; Aktay Ayaz, Nuray; et al. (Frontiers in Pediatrics, 2022)
Objective: The study aimed to report the efficacy and safety of anakinra treatment in patients with refractory multisystemic inflammatory syndrome in children (MIS-C). Methods: This is a cross-sectional retrospective study consisting of pediatric patients diagnosed with MIS-C who were treated with anakinra. Results: Among the 378 patients diagnosed with MIS-C, 82 patients (21.6%) who were treated with anakinra were included in the study. The median age of patients was 115 (6-214) months. The median duration of hospitalization was 15 (6-42) days. Sixty patients (73.1%) were admitted to the pediatric intensive care unit. Patients were treated with a median dose of 2.7 mg/kg/day anakinra concomitant with IVIG and steroids. Intravenous anakinra was applied to 12 patients while 70 patients received it subcutaneously. Twenty-eight patients required high dose (4-10 mg/kg/day) anakinra. The median day of anakinra initiation was 2 (1-14) days and the median duration of anakinra use was 7 (1-41) days. No injection site reactions were observed while elevated transaminase levels were detected in 13 patients. Seventy-three patients (89.1%) were discharged without any sequela or morbidity. Seven patients (1.8%) died. Abnormal echocardiographic findings continued in two patients (2.4%) (coronary artery dilatation in one, low ejection fraction in one) at discharge and became normal on the 2nd month. Conclusion: Based on the results of the study, anakinra was associated with clinical improvements and was safe for most patients with refractory MIS-C.